וידוי הריגה: וידויי חיילים וחיילות בסרטים תיעודייםאוטוביוגרפיים ישראליים - בכר, שירלי; סובל, אילנה (מכאן, 2017)
Visual culture that depicts war and occupation is familiar in the Israeli cultural lexicon. Nevertheless, in the last decade, a significant aspect has been added to it, as we have been exposed to various works of video art and documentary films presenting confessions of soldiers, both men and women, about their experiences in combat army service in the Occupied Territories and in wars. This article explores the cultural and ethical implications of this central cinematic phenomenon. Focusing on shame, blame, narration and subjectivization, the article looks at the juxtaposition of gender, complicity, and national identity in its cinematic representation. Examining the aesthetics and ideologies of these films, it unearths the attitudes towards Israeli acts and decisions that the cinematic medium depicts and the main ethical issues that it raises. Szobeland Bahar argue that the films harness a national perspective of what is called "an internal investigative committee," where the gatekeepers of Zionism and Israel aspire to investigate themselves and the militarist nationalist system that they endorse and maintain. Thus, the article explores questions such as to what extent do these documentaries challenge Israeli nationalism? How does genderplay out within these cinematic forms of confession? And in what way are the continuous reproductions and reinterpretations of myth and traumatic memories incorporated into the establishment of Israeli culture?